Shari'a and the Constitution in Contemporary Legal Models - Ramaioli, Federico Lorenzo. author. aut Link
XXVII, 283 p.
Keywords: GLOBAL ISSUES Series Editors: Jim Whitman · Paolo D. Farah This comparative law book aims at formulating a new analytical approach to constitutional comparisons, assuming as a starting point the different legal perspectives implied in the (Sunni) Islamic outlook on the juridical phenomena and the Western concept of law, with particular reference to constitutionalism. The volume adopts a wider and comprehensive viewpoint, comparing the different ways in which the Islamic sharī ʿa and Western legal categories interact, regardless of substantive contents of specific provisions, thus avoiding conceptual biases that can sometime affect present literature on the matter. The book explores the various dynamics subtended to the interactions between sharī ʿa and Western constitutionalism, providing a new classification to the different contemporary models. The philosophical and legal comparisons are analyzed in a dynamic way, based on a wide range of contemporary constitutional systems, virtually encompassing all the States in which Sunni Islam plays a major cultural role, and taking also into consideration non-State actors and non-recognized actors. Federico Lorenzo Ramaioli, PhD, is an Italian diplomat and lawyer,presently serving as Deputy Head of the Mission of the Italian Embassy to Doha, Qatar. He is Senior Research Associate at gLAWcal. In the past, he worked for two years with the Catholic University of Milan in the fields of Philosophy of Law and Legal Methodology. After entering the diplomatic service, he continued his research activity in law, with particular reference to the Muslim world and to the Far East. He is the author of Islamic State as a Legal Order (Routledge, 2022) and has published various articles in peer-reviewed journals, including Journal of Comparative Law, Suffolk Law Review, Rivista della Cooperazione Giuridica Internazionale, and Orientalia Parthenopea.